LINGUOSTYLISTIC INTERPRETATION OF MARKO CHEREMSHYNA’S NOVELLA “ZA MACHUKHU MOLODENKU” (“FOR THE YOUNG STEPMOTHER”) - Стефурак , Р. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of interpretation of drama text, the selection of linguistic elements of different levels is analyzed according to author’s intentions and the methods of realization of explicit and implicit of language means are watched.